2012
DOI: 10.3109/07420528.2012.686946
|View full text |Cite
|
Sign up to set email alerts
|

Morningness: Protective Factor for Sleep-Related and Emotional Problems in Childhood and Adolescence?

Abstract: The relationship between morningness/eveningness, sleep, and psychological problems is well documented in adults as well as in adolescents. However, research on the circadian orientation and its concomitants in younger children is scarce. The authors investigated the distribution of morningness/eveningness and its connection to sleeping and psychological problems in 91 children and 151 adolescents in Austria. The authors found that morning (M) types had less sleep-related and psychological problems than interm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
2
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 57 publications
0
16
2
2
Order By: Relevance
“…Concerning the onset of the association between circadian preference and externalizing symptomatology, explicitly whether there is a covariance with pubertal development, the results, as mentioned earlier, appear ambiguous. While Gelbmann et al (2012) demonstrated an association in the expected direction only in adolescents of $14 years in comparison to a sample of children aged 9 years on average, the results of Harada et al (2007) revealed an opposing trend, with significantly higher anger scores in evening-typed children between 6 months and 6 years of age and no significant differences in older children and adolescents aged up to 15 years.…”
Section: Evaluation/integration Of the Current State Of Researchcontrasting
confidence: 49%
See 3 more Smart Citations
“…Concerning the onset of the association between circadian preference and externalizing symptomatology, explicitly whether there is a covariance with pubertal development, the results, as mentioned earlier, appear ambiguous. While Gelbmann et al (2012) demonstrated an association in the expected direction only in adolescents of $14 years in comparison to a sample of children aged 9 years on average, the results of Harada et al (2007) revealed an opposing trend, with significantly higher anger scores in evening-typed children between 6 months and 6 years of age and no significant differences in older children and adolescents aged up to 15 years.…”
Section: Evaluation/integration Of the Current State Of Researchcontrasting
confidence: 49%
“…At a global level, all the studies that have been discussed throughout the course of this review lend support to some kind of association between diurnal preference and externalizing behaviors, sometimes isolated but in a majority of reports accompanied by an array of diverse psychopathology. Merely the results that Gelbmann et al (2012) reported concerning younger children conflict the theory of a higher proneness of eveningtyped children and adolescents toward anger states and aggressive conduct. However, some methodological aspects have to be addressed.…”
Section: Evaluation/integration Of the Current State Of Researchcontrasting
confidence: 45%
See 2 more Smart Citations
“…Teens who categorize themselves as having an evening preference have more daytime complaints (such as attention problems, poor school achievement, and becoming emotionally upset) than other nonevening types [34]. Self-described "morning -type" adolescents have shown fewer waking problems and female morning types appear to show less externalizing and internalizing problems [36]. Furthermore, when examining the role of both sleep deprivation and chronotype on emotions (e.g.…”
Section: The Consequences Of Sleep Disturbance During Adolescencementioning
confidence: 99%